2018
DOI: 10.1111/cp.12123
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of acceptance and commitment therapy for irritable bowel syndrome: A preliminary analysis of treatment outcomes and processes of change

Abstract: Background The aim of this study was to investigate the efficacy and proposed processes of change of acceptance and commitment therapy (ACT) in improving the outcomes of irritable bowel syndrome (IBS). Methods A total of 56 consecutive patients recruited from a specialist clinic were included in the study and completed an ACT treatment protocol (one‐day group workshop plus self‐help manual). Assessments of process (acceptance of IBS) and outcome variables (symptom severity, avoidance behaviours, quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Moreover, we found clinically relevant improvements in physical health (primary outcome) as well as significant improvements on most secondary outcomes. The findings are in accordance with the previously reported positive impact of psychological treatment on symptom load and functioning in children and adolescents with FSS [24][25][26]28] and of ACT-based interventions in adults with FSS [29][30][31]. However, it can be questioned whether the positive changes seen in this uncontrolled study can be explained solely by the Mean at different time points as well as change from baseline to follow-up and from group-start to follow up with inclusion of effect sizes Abbreviations alphabetically presented: AFQ-Y8 avoidance and fusion questionnaire, thorough assessment and psychoeducation, as seen in an RCT in youth with CFS [83].…”
Section: Principal Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we found clinically relevant improvements in physical health (primary outcome) as well as significant improvements on most secondary outcomes. The findings are in accordance with the previously reported positive impact of psychological treatment on symptom load and functioning in children and adolescents with FSS [24][25][26]28] and of ACT-based interventions in adults with FSS [29][30][31]. However, it can be questioned whether the positive changes seen in this uncontrolled study can be explained solely by the Mean at different time points as well as change from baseline to follow-up and from group-start to follow up with inclusion of effect sizes Abbreviations alphabetically presented: AFQ-Y8 avoidance and fusion questionnaire, thorough assessment and psychoeducation, as seen in an RCT in youth with CFS [83].…”
Section: Principal Findingssupporting
confidence: 92%
“…Recent reviews show that psychological interventions, particularly based on cognitive behavioural therapy (CBT) principles, are effective for FSS in children and adolescents in reducing symptom load, disability and school absence [24,25]. Acceptance and commitment therapy (ACT) is a newer development within CBT that has shown promising results in children and adolescents with chronic pain [26][27][28] and in adults with various FSS [28][29][30][31]. The overall aim of ACT is to change how the individual reacts to unwanted inner experiences by broadening the behavioural repertoire, to facilitate more adaptive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, given that acceptance is a highly trainable behavioural construct through Acceptance and Commitment Therapy, it stands to reason that the development and use of this intervention in IBS would prove of great clinical benefit. Two preliminary studies focusing on ACT for IBS (Ferreira, Gillanders, Morris, & Eugenicos, 2018;Gillanders et al, 2017) do seem to suggest that changes in IBS acceptance are at the core of improvements in the quality of life of IBS patients. In fact treatment related changes in IBS specific avoidance behaviours and Gastrointestinal anxiety in Ferreira, Gillanders, Morris, & Eugenicos (2018) are both dependent on changes in IBS acceptance, which would fit with the proposed model of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Two preliminary studies focusing on ACT for IBS (Ferreira, Gillanders, Morris, & Eugenicos, 2018;Gillanders et al, 2017) do seem to suggest that changes in IBS acceptance are at the core of improvements in the quality of life of IBS patients. In fact treatment related changes in IBS specific avoidance behaviours and Gastrointestinal anxiety in Ferreira, Gillanders, Morris, & Eugenicos (2018) are both dependent on changes in IBS acceptance, which would fit with the proposed model of this paper. In Gillanders et al (2017) only Gastrointestinal anxiety was shown to be affected by IBS acceptance, however this seemed to be constricted by the findings that only the IBS willingness component of acceptance was significantly changing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation